Application of Jurisprudential Inquiry Model Through PKn Learning to Grow Student Law Consciousness as Citizens - Robby Xandria Mustajab; Dwi Iman Muthaqin (Department of Civic Education, 2020)
This study aims to determine how effective the application of the jurisprudential inquiry model is in increasing students' enthusiasm in the learning process in the classroom, as well as to foster legal awareness of students as citizens in an era of increasingly rapid social change. The approach of this research is carried out by a mixed approach (mix method), the method used in this study is the Classroom Action Research method. This research was conducted on students of class X MIPA 5 SMA Negeri 14 Bandung as a research sample. This research model uses the Kemmis and Taggart models.The results of the study show that the application of the jurisprudential inquiry model can foster legal awareness of students as citizens. Judging from the change in behavior of students who initially majority often skipped PKn lessons or in other words had low legal awareness by not obeying school discipline, became so enthusiastic about attending PKn lessons. The jurisprudential inquiry learning model also enables students to think critically and be sensitive to various social issues and then be able to position themselves as students or as citizens of Indonesia.